PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN PENGENDALIAN INTERN SERTA KOMITMEN ANGGARAN TERHADAP KINERJA SKPD PROVINSI SULAWESI TENGGARA - Yuan Swastika (Jurnal Riset Bisnis Indonesia, 2014)
Theaims of the study are to examine and analyze the impact of variables: Budgetary Participationand Performance internal control of working units, the budget commitment and performance workunit area. This research was conducted with the census method by distributing questionnaires to 64people were selected as sample. The results of the study research show that budgetary participationsignificantly has a positive impact ont he budget commitments, budget participation significantly hasa positive impact onthe performance ofthe work unit area. As well as budgetary commitment has apositive impact on the performance signifikan working units.Keywords: Budgetary Participation, Commitment and Performance Budgeton education